Penerapan Kebijakan Upah Minimum Provinsi dan Pengaruh Upah Terhadap Motivasi Kerja pada PT. Kontraktor Nurhalisa Abadi Kabupaten Manokwari Provinsi Papua Barat - Nurliana Said; Elina Relawaty Situmorang; Siti Aisah Bauw (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2022)
This study aims to analyze the application of the Provincial Minimum Wage and the Effect of Wages on Work Motivation at PT. Contractor Nurhalisa Abadi, Manokwari Regency, West Papua Province. The research approach used is a quantitative research approach with data analysis methods used, namely descriptive statistics and simple linear regression models with SPSS version 26 program. The results of descriptive statistical research show that the UMP at PT. Contractor Nurhalisa Abadi is applied 100%, then the results of simple linear regression show that the partial test (t test) of wages has a positive and significant effect on employee motivation at PT. Contractor Nurhalisa Abadi where this affects the company's productivity.